Considering Space A Critical Concept for the Social Sciences - Bartmanski, Dominik; Füller, Henning; Hoerning, Johanna; Weidenhaus, Gunter (Taylor & Francis, 2024)
Considering Space demonstrates what has changed in the perception of space within the social sciences and how useful - indeed indispensable - this category is today. While the seemingly deterritorializing effects of digitalization might suggest that space is a secondary consideration, this book proves such a presumption wrong, with territories, borders, distances, proximity, geographical ecologies, land use, physical infrastructures - as well as concepts of space - all being shown still to matter, perhaps more than ever before. Seeking to show how society can and should be perceived as spatial, it will appeal to scholars of sociology, geography, architecture and urban studies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. Funded by the DeutscheForschungsgemeinschaft (DFG, German Research Foundation) - Projektnummer 290045248 - SFB 1265.